Peningkatan Pengetahuan dan Kemampuan Kader Posyandu dalam Stimulasi I Ntervensi dan Deteksi Dini Tumbuh Kembang Anak di Kelurahan Hadimulyo Barat Kota Metro - Riyanto; Herlina Herlina; Islamiyati Islamiyati (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2021)
The golden period of growth and development of children occurs from the beginning of pregnancy until birth and children are 2 years or 1000 days. The impact of children not being stimulated can be growth disorders and delays. The problem of delays or deviations in child development is still a problem for children in Indonesia. The role of cadres needs to be increased to stimulate early detection and early intervention of developmental deviations. This activity aims to improve the knowledge and skills of cadres in early stimulation and intervention for growth and development, so as to be able to find early developmental deviations in toddlers. This activity uses a training method with education using modules and simulations using a developmental pre-screening questionnaire. The participants of the activity were the Melati Cadre and Kenanga Cadre totaling 14 people and 19 infants under five in the West Hadimulyo sub-district, Metro Central district, Metro city. Evaluation of activities was carried out by pre-test and post-test and assessment of the skills of cadres to stimulate development using developmental pre-screening questionnaires. The results of the activity obtained increased knowledge and skills of Integrated Service Post cadres to stimulate development with a developmental pre-screening questionnaire. The enthusiasm of the cadres in this activity and the support of partners, so that the activity can be smooth and successful. It is necessary to follow up the implementation of cadre skills directly during early stimulation activities and interventions for the growth and development of children of various ages